Mitos dalam Novel Kehilangan Mestika Karya Fatimah Hasan Delais - Salwa, Siti Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research study focuses on the analysis of the myths contained in the novel Jenis Mestika by Fatimah H. Delais, or commonly known as Hamidah. The aim of this research is to find out what myths contained in the novel Pesan Mestika are believed by the public. The method used in this research is a qualitative descriptive method, meaning that the data collection process is carried out by recording all forms of myth contained in the novel and then explaining them again in the form of words or sentences. The results obtained after conducting this research were that 5 related data were found in the novel Kehilangan Mestika.